Thyroid Dysfunction and Cholesterol Gallstone Disease - Kube, Irina; Zwanziger, Denise (Experimental and Clinical Endocrinology & Diabetes, 2019)
Cholesterol gallstone disease (CGD) affects 10–15% of the adult population worldwide and the prevalence increases as a result of longer life expectancy as well as rising obesity in the general population. Beside well established CGD risk factors including environmental and genetic determinants (LITH genes), a correlation between thyroid dysfunction and CGD has been suggested in several human and murine studies. Although the precise underlying mechanisms are poorly understood, thyroid hormones may impact bile flow, bile composition and the maintenance of the enterohepatic circulation. Further there is evidence that thyroid hormones possibly impact LITH genes which are regulated by nuclear receptors (NRs). A better understanding of the CGD pathomechanisms might contribute to personalized prevention and therapy of highly prevalent and economically significant digestive disease. This review presents the current knowledge about the association between CGD and thyroid hormone dysfunction.
Keywords: bile; cholesterol gallstone disease; detoxification; enterohepatic circulation; lipid homeostasis; LITH genes; nuclear receptors; thyroid dysfunction; thyroid hormone